2004
DOI: 10.1242/jcs.01543
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ryanodine receptor 1 in fast skeletal muscle fibers induces a fast-to-slow muscle fiber type transition

Abstract: Skeletal muscle fiber type is regulated by innervation-induced cell signaling including calcium release mechanisms that lead to transcriptional activation of fiber type-specific genes. Avian fast pectoralis major (PM) and slow medial adductor (MA) muscles differentially control expression of the slow myosin heavy chain 2 (slow MyHC2) gene. We report here that slow MyHC2 gene expression in fast PM muscle fibers is repressed by endogenous activity of the ryanodine receptor 1 (RyR1). Inhibition of RyR1 with ryano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
(64 reference statements)
1
27
0
Order By: Relevance
“…K ϩ -depolarized C2C12 cells present the same dependence, with an important role for extracellular Ca 2ϩ as well (32). Other studies, performed in C2C12 cells and cultured avian skeletal muscle fibers, have reported a role for both RyR and IP 3 R-mediated Ca 2ϩ release in NFAT activation (20,21,35).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…K ϩ -depolarized C2C12 cells present the same dependence, with an important role for extracellular Ca 2ϩ as well (32). Other studies, performed in C2C12 cells and cultured avian skeletal muscle fibers, have reported a role for both RyR and IP 3 R-mediated Ca 2ϩ release in NFAT activation (20,21,35).…”
mentioning
confidence: 63%
“…A mutagenesis study (19) has indicated that both NFAT and MEF2 binding sites are required for innervation-induced MyHC2 promoter activity in slow muscle fibers. Basically, there is NFAT activation by RyR inhibition (20), whereas IP3R blockade results in the opposite effect (21). These results might reflect complex mechanisms of NFAT regulation in another developmental stage as well as differences with respect to the stimulatory pattern used.…”
Section: Discussionmentioning
confidence: 99%
“…In adult muscles, dystrophin and α-syntrophin regulate PLC activity by stabilizing the sarcolemma; thus, dystrophin absence leads to increased PLC activity (Jordan et al, 2004;Mondin et al, 2009;Sabourin et al, 2012). Furthermore, previous studies showed that dystrophic human samples and murine cell lines expressed high levels of IP3 compared with normal cell lines (Liberona et al, 1998;Mondin et al, 2009) and IP3-induced Ca 2+ release altered gene expression regulation (Powell et al, 2001;Araya et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…RyR1 inhibition increases slow MyHC2 promoter activity in innervated pectoralis major (PM) muscle fibers, enhances the D r a f t transcriptional activity of nuclear factor of activated T cells and myocyte enhancer factor 2, and enhances their interactions with their respective binding sites on the slow MyHC2 promoter; these results reveal that RyR1 activity in innervated fast PM muscle fibers contributes to cell type-specific repression (Jordan et al 2004). ERBB4 is a receptor for neuregulins that belongs to a family of closely related proteins implicated as regulators of neural and muscle development and the differentiation and oncogenic transformation of mammary epithelia (Carraway and Burden 1995;Plowman et al 1993).…”
Section: Discussionmentioning
confidence: 99%